Ensign Pulver [videorecording (DVD)] - Logan, Joshua; Walker, Robert, 1940-2019-; Ives, Burl, 1909-1995; Matthau, Walter; Sands, Tommy, 1937- (Archive collection., 2010)
"Sign on for a lighthearted, seeworthy oceangoing comedic voyage that begins where the classic Mister Roberts left off. Doug Roberts is gone, but feckless Frank Pulver (Robert Walker) remains to battle boredom aboard the World War II-era cargo ship Reluctant. His weapons range from a slingshot to a surgical scalpel. His target is the tyrannical captain (Burl Ives). His cohort is the genial keeper of the joy juice, Doc (Walter Matthau). And his aim is hilariously true"--Container.